Peran Desa Adat dalam Upaya Penanggulangan Kekerasan Seksual Terhadap Anak di Kabupaten Buleleng - Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku (Universitas Muhammadiyah Surabaya, 2023)
This research is based on the issue of the rampant cases of child sexual violence occurring in Buleleng Regency. The questions to be answered as the objectives of this research are: (1) how are the legal regulations governing the role of traditional villages in efforts to combat child sexual violence?; and (2) what is the role of traditional villages in efforts to prevent child sexual violence in Buleleng Regency? The research method used is empirical legal research of a descriptive nature. The data and data sources used in this study are primary and secondary data. Data collection techniques used in this study are document study, observation, and interviews. The sample determination technique used in this study is non-probability sampling with purposive sample as the sample type. The data collected in this study is further constructed qualitatively and presented descriptively. The results of this study found that: (1) the regulation regarding the role of traditional villages in efforts to prevent child sexual violence is not explicitly regulated in the Child Protection Act, the Sexual Violence Act, and related regulations at the provincial and Buleleng Regency levels; and (2) the role of traditional villages in efforts to prevent child sexual violence in Buleleng Regency is not very significant. This is due to the lack of specific legal basis regulating the role of traditional villages in preventing child sexual violence.